Edukasi dan Penerapan Bromage Score dalam Penilaian Mobilitas Pasien Pasca Spinal Anestesi di Rumah Sakit - Dwi Handoyo; Siti Sarifah (Jurnal Pengabdian Masyarakat Nusantara, 2021)
Spinal anesthesia is a widely used anesthetic technique, particularly in surgeries involving the lower body, due to its effectiveness and safety profile. A critical component of post-spinal anesthesia recovery is the assessment of patient mobility, which can be quantitatively measured using the Bromage Score. The Bromage Score evaluates the degree of motor block, which is essential for determining when a patient can safely begin mobilizing after anesthesia. The education and implementation of the Bromage Score in hospitals are designed to enhance healthcare professionals' understanding of its significance, ensuring a more objective and systematic approach to patient recovery monitoring. This educational program involves a structured training session for healthcare workers, distribution of educational materials such as brochures and manuals, and evaluations both before and after the intervention to assess changes in knowledge and application. The results of the program indicate a significant increase in healthcare professionals’ understanding of how to apply the Bromage Score and improved quality in the monitoring of patient mobility after spinal anesthesia. The consistent and accurate implementation of the Bromage Score is crucial as it helps medical personnel determine an appropriate and safe time for patient mobilization, thus reducing the risk of complications such as falls, orthostatic hypotension, or delayed recovery. As a result, the program is recommended as a standard practice in healthcare settings to improve post-spinal anesthesia recovery outcomes and patient safety.